Performance of the single‐event wind erosion evaluation program (SWEEP) model in assessing the impact of crop rotation, green manure, fertilizer, and tillage on wind erosion. (23rd June 2022) - Pi, Huawei; Webb, Nicholas P.; Huggins, David R.; Sharratt, Brenton; Li, Sisi
Abstract: Agricultural land management strategies have been applied to minimize wind erosion in the inland Pacific Northwest (iPNW) due to their profound influence on various soil properties and crop residue characteristics. However, simulating soil loss in response to these treatment strategies remains a challenge. The objective of this study was to test the performance of the single‐event wind erosion evaluation program (SWEEP) in simulating soil loss from agricultural land under contrasting tillage, crop rotation, fertilizer, and green manure treatments in the iPNW. These management strategies appeared to impact residue characteristics but had little or no impact on soil properties except tillage treatments in the short term (<2 years). Tillage appeared to have a greater impact on soil properties and residue characteristics than other treatments. As a result, the performance of SWEEP varied among disk‐tillage (DT), undercutter‐tillage (UT), and NT (no‐tillage/zero‐tillage) treatments. No or little difference was found in the performance of SWEEP between winter wheat‐summer fallow (WW‐SF) and WW‐oilseed‐SF (WW‐O‐SF) crop rotations and synthetic and biosolids fertilizer treatments. In addition, the performance of SWEEP was acceptable for both crop rotation and fertilizer treatments. In contrast, poor agreement between simulated and measured erosion was found for manure treatments in which SWEEP over‐estimated erosion by 313 and 210% for no manure and manure treatments, respectively. The over‐estimation of SWEEP may be due to the over‐estimation of abrasion flux from the fully crusted soil surface. Our results suggest that SWEEP can be used to identify control measures for windblown soil loss in the iPNW.